The utilization of aluminum waste as sand reinforcement in concrete - Cik Roziana Hibadullah (School of Environmental Engineering, University Malaysia Perlis, 2013)
A study was conducted on the use of recyclable aluminum materials, as sand replacement material in concrete mix with replacement of 1%, 2% and 5%.